THE EFFECT OF MOTIVATION AND WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE (CASE STUDY IN A TELECOMMUNICATIONS COMPANY IN THE CITY OF BANDUNG) - Riyan Ferdiansyah; Nenny Rinawati (STMIK Mardira Indonesia, Bandung, 2022)
Researchers conducted research intending to determine the effect of Motivation and Work Environment on Employee Performance in one of the telecommunications companies in the city of Bandung. Furthermore, this research analyzes the factor that has the most dominant influence between motivation and works environment on employee performance in one of the telecommunications companies in the city of Bandung, which is the object of research of as many as 95 employees using a questionnaire.Based on research using path analysis, the variables of motivation and work environment on employee performance in one of the telecommunications companies in the city of Bandung are valid. The conclusions and considering the relationship with the study results are paying attention to motivation and work environment to improve employee performance.Keywords: Motivation, Work Environment, Employee Performance